Courteous love and fashion the construction of another social world (ModaPalavra e-periódico, 2008)
The present article discusses the historical context of establishtion of the fashion system starting from the analysis of the courteous love, understanded as a seduction strategy and this as the preponderant form of social-historical association with the feminine. It ends that, subverted the form relationships base among the subjects - the physical force - the European western society became more feminine and in this the fulcrum point resides to the historical of the appearance of the fashion interpretation partner.
Keywords: courteous love; fashion; history